Transport of malonate in a goethite–silica sand system - Filius, Jeroen D; Meeussen, Johannes C.L; van Riemsdijk, Willem H (Colloids and surfaces. A, Physicochemical and engineering aspects, 1999)
The mobility of weak organic acids is of great importance for the transport of heavy metals and other contaminants. This work discusses the breakthrough behavior of malonic acid through a column packed with goethite coated sand. The transport of malonic acid is dominated by multicomponent chemical interactions of protons and the malonic acid on the goethite surface and in solution. The experimental results show a fast breakthrough and a slow desorption of malonate. The binding capacity of the goethite coated silica sand column for malonic acid and acidity are discussed and their impact on elution is illustrated. The data have been predicted with a combination of the CD-MUSIC model and a one-dimensional convective-dispersive transport code. Reasonable agreement was obtained between data and model predictions.